2015
DOI: 10.1364/oe.23.015390
|View full text |Cite
|
Sign up to set email alerts
|

Broadband and wide angle infrared wire-grid polarizer

Abstract: An infrared polarizer consisting of metal-insulator-metal (MIM) gratings is designed with transmittance exceeding 85% and polarization extinction ratio (ER) higher than 70 dB in the wavelength range from 1.5 to 8 μm. Moreover, the polarizer retains excellent performance even when the incident angle increases to as large as 80°. The MIM gratings support magnetic polariton (MP) in the near-infrared regime and operate non-resonantly in the mid-infrared regime, both of which result in the advantages of high extinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…It can be found that ER usually presents a tendency of linear climb with the increment in the metal thickness, as shown in Figure 1c and S1, Supporting Information. The same conclusion can also be found in some references, [13b,18,31] but the thickness of the wire grid in these articles does not reach the level designed in this work. In ideal simulation, the results of ER can even reach more than 100 dB, as shown in Figure S1b, Supporting Information.…”
Section: Design and Simulationsupporting
confidence: 81%
See 1 more Smart Citation
“…It can be found that ER usually presents a tendency of linear climb with the increment in the metal thickness, as shown in Figure 1c and S1, Supporting Information. The same conclusion can also be found in some references, [13b,18,31] but the thickness of the wire grid in these articles does not reach the level designed in this work. In ideal simulation, the results of ER can even reach more than 100 dB, as shown in Figure S1b, Supporting Information.…”
Section: Design and Simulationsupporting
confidence: 81%
“…[ 17 ] Some articles also propose high aspect ratio structures to improve the extinction ratio, but do not fabricate actually. [ 18 ] The main reason is that fabricating uniform wire grid with high aspect ratio on a large area is very difficult. However, we fabricate this structure via a new high‐power inductively coupled plasma (ICP) fast etching formula successfully.…”
Section: Introductionmentioning
confidence: 99%
“…However, this kind of polarizers can only work in narrow angle ranges (nearby the Brewster angles) [23][24][25]. To achieve wide-angle high-performance polarizers, researchers proposed a series of twodimensional (2D) and three-dimensional (3D) nanostructures, including wire-grid gratings [26][27][28][29], metasurfaces [30][31][32][33][34] and helix arrays [35][36][37][38]. However, fabrication of 2D and 3D nanostructures operating at optical wavelengths generally requires lithography, which greatly increases the complexity and cost of fabrication [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the traditional prism polarizers, wire grid polarizers have potential for miniaturization and integration of the optical devices, which have been widely applied to many fields, including liquid-crystal display [1][2][3][4][5], imaging [6][7][8], beam splitters [5,9] and bio-detection [10]. The wire grid polarizers in the infrared [11][12][13][14][15][16][17] and terahertz [18][19][20][21][22] spectral range have been reported widely. Recently, the polarizing elements working at shorter wavelengths have received growing attention.…”
Section: Introductionmentioning
confidence: 99%